Identify the Disaster Nursing Training and Education Needs for Nurses in Taif City, Saudi Arabia - Brinjee D; Al Thobaity A; Almalki M; Alahmari W (Dove Medical Press, 2021)
Duaa Brinjee,1 Abdulellah Al Thobaity,2 Mohammed Almalki,2 Waleed Alahmari2 1Nursing Department, Al Noor Hospital, Makkah, Makkah Region, Saudi Arabia; 2Nursing Department, Applied Medical Sciences, Taif University, Taif, Makkah Region, Saudi ArabiaCorrespondence: Abdulellah Al ThobaityNursing Department, Applied Medical Sciences, Taif University, Taif, Saudi ArabiaEmail a.thobaity@tu.edu.saIntroduction: Nursing is considered the healthcare profession with the most members. Emergency nurses constitute the first line of treatment in healthcare facilities when catastrophic events bring disaster victims in need of medical attention. Therefore, these nurses must be well educated and trained efficiently to be able to deal with disastrous situations properly. This study aimed to distinguish the most important elements of education and training for preparing emergency nurses to face disasters in the Kingdom of Saudi Arabia (KSA), specifically, the city of Taif.Methods: This study employed a tool to measure nurses’ most important training and education needs that was created by the authors based on a literature review and was approved by an expert panel in disaster nursing. Questionnaires were distributed to emergency nurses in four hospitals run by the Ministry of Health in Taif city. Survey responses were received from 210 participants, and the data were analyzed using a principal component analysis (PCA). A one-way ANOVA was used to determine the differences between groups according to their experiences.Results: The following three factors were extracted from the data after redundant items were loaded and excluded: incident management systems (IMSs), disaster triage, and disaster drills. Nurses with less than three years of experience have a significant need to learn about these elements in order to be able to cope with disasters.Conclusion: Understanding different types of disasters and how to deal with these catastrophic events is crucial. Significant differences existed between ED nurses in their understanding of the basic elements of disaster management based on their level of experience in an ED. Therefore, disaster education must be included in nursing curricula, and more training courses, mock drills, and simulations must be conducted in hospitals for nurses, especially nurses with less experience, so they can learn to manage their responsibilities during disasters.Keywords: disaster nursing, disaster education, disaster training, disaster preparedness